2009
DOI: 10.1007/s11071-009-9503-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of an inertial two-neuron system with time delay

Abstract: In this paper, we considered a delayed differential equation modeling two-neuron system with both inertial terms and time delay. By analyzing the distribution of the eigenvalues of the corresponding transcendental characteristic equation of its linearized equation, local stability criteria are derived for various model parameters and time delay. By choosing time delay as a bifurcation parameter, the model is found to undergo a sequence of Hopf bifurcation. Furthermore, the direction and the stability of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…In this case, Liu et al [30] had made a detailed analysis on the effect of time delay on the Hopf bifurcation. They have clearly shown that the system (1.1) undergo a sequence of Hopf bifurcation when the time delay cross a critical value.…”
Section: Lemma 22mentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, Liu et al [30] had made a detailed analysis on the effect of time delay on the Hopf bifurcation. They have clearly shown that the system (1.1) undergo a sequence of Hopf bifurcation when the time delay cross a critical value.…”
Section: Lemma 22mentioning
confidence: 99%
“…In details, one can see [1,. In 2009, Liu et al [30] had dealt with the dynamics (including the stability, local Hopf bifurcation and resonant codimensional-two bifurcation) of the following inertial two-neuron system with time delay…”
mentioning
confidence: 99%
“…In recent years, the stability analysis and the feedback control of time delay systems have been widely investigated since delays are often encountered in various engineering systems (see, i.e., [29][30][31][32][33][34][35]). On the other hand, descriptor systems with or without time delay have been extensively studied in recent years (see, i.e., [11,14,[17][18][19][20][21][22][23][24]27], and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In [15], the stability of bifurcating periodic solutions is discussed for a single delayed inertial neuron model under periodic excitation. Liu et al [16] studied the effect of time delay on dynamical behaviors of a two-neuron inertial system. For a four-neuron delayed inertial system [17], Hopf bifurcation was investigated and chaotic behavior was observed in.…”
Section: Introductionmentioning
confidence: 99%